The Role of Hydration and N-Acetyl Cysteine Combination in 48 Hours Contrast-Induced Nephropaty after Percutaneous Coronary Intervention in Stage Three Chronic Kidney Disease Patients - Lydia D Simatupang; Endang Susalit; Ika Prasetya Wijaya (Jurnal Penyakit Dalam Indonesia)
Introduction. Contrast Induced Nephropathy (CIN) after percutaneous coronary intervention (PCI) is common in stage 3 chronic kidney disease (CKD) patients. While there is no cure for CIN and some cases are fatal for the kidney or even life, it is preventable. Eventhough controversial, hydration and N-Acetyl Cysteine (NAC) are modalities to prevent CIN. Not having a certain guideline to prevent CIN in Integrated Cardiac Services (ICS) Cipto Mangunkusumo Hospital for PCI patients generates interest to study it.